Effect of urea–formaldehyde nanoparticles on the barrier property and delamination resistance for epoxy coating. Issue 5 (28th August 2021) - Li, Zhe; Zheng, Hongpeng; Liu, Li; Meng, Fandi; Cui, Yu; Wang, Fuhui
Abstract : Purpose: The purpose of this paper is to investigate the effect of urea–formaldehyde (UF) nanoparticles on the barrier property and delamination resistance for epoxy coating in a 3.5% NaCl aqueous solution. Design/methodology/approach: The UF resin was synthesized via sol–gel method, and UF/epoxy composite coating was prepared through ball-milling process; the microstructure and chemical composition of UF resin were observed using the Fourier transform infrared spectroscopy, scanning electron microscopy and transmission electron microscopy; the bonding strength of coating/metal interface was investigated through adhesion test; the mechanical properties of the coatings were studied by tensile tests; and the barrier and corrosion resistance properties were verified using salt spray test, cathodic delamination test and electrochemical impedance spectroscopy measurements. Findings: The experimental results indicated that the UF resin presented uniformly dispersed nanoparticles in the epoxy matrix and enhanced the bonding strength of coating/metal interface and then improved the delamination resistance for composite coating, which resulted in the enhancement of the barrier property and corrosion resistance for UF/epoxy composite coating. Originality/value: In this paper, an easily prepared blending compounding coating with excellent corrosion resistance property was synthesized via sol–gel method and ball-milling process. The effects of UF nanoparticles on the barrier property and delamination resistance were investigated in detail.